Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1073/pnas.86.20.7746
|View full text |Cite
|
Sign up to set email alerts
|

Sensory rhodopsins I and II modulate a methylation/demethylation system in Halobacterium halobium phototaxis.

Abstract: This work demonstrates that phototaxis stimuli in the archaebacterium Halobacterium halobium control a methylation/demethylation system in vivo through photoactivation of sensory rhodopsin I (SR-I) in either its attractant or repellent signaling form as well as through the repellent receptor sensory rhodopsin II (SR-Il, also called phoborhodopsin). (14) and phototaxis behavior (15). A clue to the mechanism of information transfer from the SR-I chromophoric protein was the finding of a methylaccepting protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 36 publications
0
45
0
Order By: Relevance
“…Halobacterial cells continually release methyl groups in volatile chemical form, and the rates of release are altered transiently by chemostimuli and photostimuli (1,19). We demonstrated that the rates of release of methanol by sensory stimuli also do not exhibit the same symmetry as those of E. coli: for halobacteria, both positive and negative stimuli result in an increased rate of methanol release (1).…”
Section: Resultsmentioning
confidence: 87%
“…Halobacterial cells continually release methyl groups in volatile chemical form, and the rates of release are altered transiently by chemostimuli and photostimuli (1,19). We demonstrated that the rates of release of methanol by sensory stimuli also do not exhibit the same symmetry as those of E. coli: for halobacteria, both positive and negative stimuli result in an increased rate of methanol release (1).…”
Section: Resultsmentioning
confidence: 87%
“…Many archaea and some bacteria have CheC or the closely related CheX (Kirby et al, 2001). Some of these have polar flagella and, on negative stimuli, undergo repeated reversals of motion, such as the spirochaete Spirochaeta aurantia (Cercignani et al, 1998;Fosnaugh & Greenberg, 1988) and the archaeon Halobacterium salinarum (Spudich et al, 1989). It is clear that the main output of the receptor/CheA complex is to regulate CheY-P levels in these as in all chemotactic bacteria/ archaea but how CheY-P levels can regulate switching frequency (it primarily affects bias) has never been understood.…”
Section: Discussionmentioning
confidence: 99%
“…Backward swimming and reversals between directions, however, occur in wild-type. The increased reversals on negative stimulus might be due to changing CheY-P levels affecting affinity of CheC (or CheX) for the switch and possibly also to changing affinity for CheC (or CheX) at the receptors (due to methylation changes that occur there: Nordmann et al, 1994;Spudich et al, 1989). As a further parallel with B. subtilis, we note that a cheB mutant of H. salinarum shows increased frequency of reversals, with no effect on the ratio of CW and CCW rotation of the flagella, compared with wild-type (Rudolph & Oesterhelt, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…A second protein was implicated by mutant analysis to be required for SR-I control of cell motility responses (18). On the basis of its reversible carboxylmethylation and other biochemical similarities to eubacterial chemotaxis transducers, the protein was proposed to function as a halobacterial transducer for SR-I, relaying signals from the receptor to cytoplasmic components controlling the flagellar motor (21). The protein, now called HtrI, was isolated, and its gene was cloned and found to reside immediately upstream of sopI (27).…”
mentioning
confidence: 99%